2021
DOI: 10.1289/ehp7696
|View full text |Cite
|
Sign up to set email alerts
|

Chlorinated Paraffin Levels in Relation to Other Persistent Organic Pollutants Found in Pooled Human Milk Samples from Primiparous Mothers in 53 Countries

Abstract: Background: The current production and use of chlorinated paraffins (CPs) at likely exceeds the lifetime production of polychlorinated biphenyls (PCBs). These persistent organic pollutants (POPs) are a concern to human health. Objectives: The United Nations Environment Programme conducts global surveys of human milk samples from individual countries as a noninvasive method of investigating levels and trends in human exposures to POPs such as CPs. We meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(19 citation statements)
references
References 47 publications
4
15
0
Order By: Relevance
“…Rates of exposure to ∑SCCPs and ∑LCCPs were similar for both age groups for both scenarios, while intakes of ∑MCCPs were estimated to be approximately 5 times greater for adults and 5.5-6 times higher for toddlers. The daily ∑CP intake estimates in this study were similar to those previously reported for Australian adults and toddlers, but higher than the rates estimated for Swedish populations [6,43] . Estimated rates of CP exposure from dust have been around 1-2 orders of magnitude greater in China, with much higher intake of SCCPs in particular [4,44] .…”
Section: Human Exposure Assessmentsupporting
confidence: 86%
See 4 more Smart Citations
“…Rates of exposure to ∑SCCPs and ∑LCCPs were similar for both age groups for both scenarios, while intakes of ∑MCCPs were estimated to be approximately 5 times greater for adults and 5.5-6 times higher for toddlers. The daily ∑CP intake estimates in this study were similar to those previously reported for Australian adults and toddlers, but higher than the rates estimated for Swedish populations [6,43] . Estimated rates of CP exposure from dust have been around 1-2 orders of magnitude greater in China, with much higher intake of SCCPs in particular [4,44] .…”
Section: Human Exposure Assessmentsupporting
confidence: 86%
“…The levels of CPs measured in the current study spanned a similar range to those determined in 44 samples of indoor dust from houses, offices, and vehicles in Brisbane and Canberra, Australia [6] . MCCPs were also the dominant group in the analysis by He et al [6] , ranging from 5.1 to 540 μg/g with a median of 95 μg/g.…”
Section: Analysis Of Real Samplessupporting
confidence: 66%
See 3 more Smart Citations